Understanding port choice behaviour: A network perspective - TANG, Loon Ching (Institutional Knowledge at Singapore Management University, 2011)
A novel Network-based Integrated Choice Evaluation (NICE) model is developed to enhance the multinomial logit preference (MNL) model that is widely employed in the existing port choice literature. The NICE model integrates the element of port service network with observational port attributes to identify important quality characteristics on which liner shipping companies base their port choices. An empirical study of the proposed model is conducted through the service schedules of three established liner shipping companies. Results show that port efficiency and scale economies are the more important dimensions influencing liner shipping companies’ selection of major Asian ports. Nevertheless, it is important for a competitive port to balance its efforts among all the dimensions.